Cost-benefit analysis of haemophilus influenzae vaccanation programme in Malaysia - Hussain, I,; HM.I.,; Syed Aljunid,; Sofiah, A.,; Ong, L.C.,; Choo, K.E.,; Musa,M.N.,; The, K.H.,; Ng, H.P., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1999)
A cross-sectional study involving five public hospitals was undertaken to examine the cost-benefit of introducing mass immunisation against Haemophillus Influenzae Type B meningitis. Out of 435 cases of clinical meningitis reported in 1995, 71 cases (16.3%) fulfilled the diagnostic criteria for meningitis. A total of 28 cases (39.4%) were due to Haemophillus influenza Type B (Hib). The average length of stay for Hib meningitis cases were 19.1 days, 10 cases (35.7%) of were admitted to ICU for ventilatory support for the average duration of 4 days. It was found that 3 (10.7%) of children with Hib meningitis died, 13 (46.4%) of them were discharged well and 12 (42.9%) developed motor deficits. In estimating the benefit of Hib immunisation programme, it is assumed that 1.2% of all paediatric admissions are due to meningitis and 50% of these meningitis cases are due to Haemophillus influenzae Type B. Only the cost of hospitalisation, cost of long-term care for those with neurological deficits and cost incurred to family during admissions are included in this study. Since the proposed programme will be corporated with the current EPI programme, except for the cost of vaccines, no additional cost was included in the calculation. The total benefits for Hib mass vaccination programme is RM 32.2 million and benefit to cost ratio is 1.09 with net benefit of RM 2.8 million. However if the number of meningitis cases detected increased by 25% and cost of vaccine is reduced by 25%, the benefit to cost ratio is estimated to be 1.82